Reclaiming abandoned railway infrastructure for post-progress times - Bianca Elzenbaumer; Flora Mammana (lo Squaderno)
We work at a train station. Not at the ticket counter, the bar, or the toilets, but at a grassroots commu- nity academy called La Foresta, located right next to the office of the railway police. We have worked here since 2017, first around and now in our local train station, as a group of actively engaged citizens, freelance educators, researchers in the wild, and change-oriented feral entrepreneurs. In this text, we share three vignettes and the respective key learnings of the collective process of creative and transformative instrastructuring that we are driving in and around the train station of Rovereto, a town with 40,000 inhabitants in the Italian Alps.